PERANCANGAN KEMBALI KANTOR DESA HUTABOHU KECAMATAN LIMBOTO BARAT KABUPATEN GORONTALO - Nurnaningsih Nico Abdul; Zuhriati A Djailani (Univeristas Negeri Gorontalo, 2022)
One of the infrastructure improvement programs in Hutabohu village is the construction of a village office and meeting hall. The implementation method is carried out in three stages 1) Primary and secondary data collection; 2) Stages of analyzing existing data and recognizing the potential in problems that arise, looking for relationships between problems so that an overview of the causes of problems arises; 3) The design stage is making design drawings which are the embodiment of ideas based on the results of the analysis that has been done previously. The results obtained are the redesign of the village office building and meeting hall to accommodate the needs of village officials and the presence of a comfortable meeting room for the village community. The hope is that the government and the community can continue this program to the development stage by means of self-management so that the community as the main actors and owners feel directly and can be fully responsible for the results of their work, so that the quality can be maximized